Widely targeted metabolomics analysis reveals the formation of nonvolatile flavor qualities during oolong tea manufacturing: a case study of Jinguanyin - Hu, Qingcai; Zheng, Yucheng; Yang, Yun; Ni, Zi-Xin; Chen, Bin; Wu, Zongjie; Huang, Huiqing; Wu, Qingyang; Zhou, Zi-wei; Gao, Shuilian; Lai, Zhongxiong; Lin, Hongzheng; et al. (Frontiers in Nutrition, 2023)
The manufacturing processes of oolong tea exert a substantial influence on its nonvolatile components, giving rise to the emergence of distinct flavor attributes. In order to comprehend the dynamics changes of nonvolatile components throughout the manufacturing stages of the Jinguanyin (JGY) cultivar and its potential mechanism for flavor formation, we conducted comprehensive metabolomics and sensomics analysis. A total of 1,005 nonvolatile metabolites were detected, and 562 were recognized as significant differential metabolites during various phases of oolong tea processing, which exhibited the most significant effects during the third turning-over, third setting, and high-temperature treatments on the nonvolatile metabolites of oolong tea. JGY finished tea presents a characteristic flavor of mellow, sweet in aftertaste, and significant Yin rhyme, which was collectively promoted by the accumulation of amino acids and organic acids, the decrease in flavonols (3-O-glycosides) and sugar substances, the alteration of phenolic acids, and the stabilization of caffeine. The results summarized the dynamic changes in various types of nonvolatile compounds during oolong tea processing, contributing to the understanding of the formation of oolong tea flavor qualities.